2019
DOI: 10.1097/coc.0000000000000557
|View full text |Cite
|
Sign up to set email alerts
|

All-Cause 30-Day Mortality After Surgical Treatment for Head and Neck Squamous Cell Carcinoma in the United States

Abstract: Objectives: Thirty-day (30-day) mortality, a common posttreatment quality metric, is yet to be described following surgery for head and neck squamous cell carcinoma (HNSCC). This study aimed to measure 30-day postoperative mortality in HNSCC and describe clinical/nonclinical factors associated with 30-day mortality. Methods: In this retrospective cohort study, the National Cancer Database (2004 to 2013) was queried for eligible cases of HNSCC (n=91,858)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In the HNC context, the prognostic importance of comorbidity is underscored by a study that demonstrated that severe comorbidity burden is as impactful on HNC survival as T4 stage tumor 43 . While our study could not assess comorbidity burden due to lack of data, this association between Medicaid and comorbidity burden previously established in other studies might be a plausible explanation for the poor outcomes seen in these patients insured under Medicaid 44 …”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…In the HNC context, the prognostic importance of comorbidity is underscored by a study that demonstrated that severe comorbidity burden is as impactful on HNC survival as T4 stage tumor 43 . While our study could not assess comorbidity burden due to lack of data, this association between Medicaid and comorbidity burden previously established in other studies might be a plausible explanation for the poor outcomes seen in these patients insured under Medicaid 44 …”
Section: Discussionmentioning
confidence: 74%
“…Second, we do not have any information on patients' comorbid conditions or smoking and alcohol habits, which would have been critical in appraising the overall health of patients at the time of diagnosis. There is reason to believe that patients under Medicaid may have greater comorbidity burden than those uninsured, 44 which might explain why they have poorer survival outcomes even when able to afford some care due to them having Medicaid 44,51 . Third, in regard to insurance status, patients coded as “insured, no specifics” for the insurance variable in SEER include patients with “Medicare/Medicare, NOS” and “Insurance, NOS.” These patients were included with patients with private insurance, but if 18–64‐year‐old patients actually had Medicaid, the point estimates of Medicaid could be biased toward the null.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age was the only other clinical variable associated with perioperative mortality. The perioperative mortality rate for all surgically treated patients with head and neck cancer was recently reported as 0.84% by Bukatko et al using the NCDB 18 . In their review, the clinical variables with the strongest relationship with perioperative mortality were CDCC and tumor stage 18 .…”
Section: Discussionmentioning
confidence: 99%
“…While sociodemographic factors such as marital status, [7][8][9] health insurance status, [10][11][12][13][14] and race/ethnicity [15][16][17][18][19][20] have been explored in HNC, it is unknown if these factors impact patients of HNC with end-stage disease. It is also unknown if there are differences in the impact of these sociodemographic factors based on whether cases are oropharyngeal vs non-oropharyngeal.…”
Section: Introductionmentioning
confidence: 99%